Physicochemical and Sensory Value of Frozen Egg Tea Drinks with Addition Carboxymethyl Cellulose (CMC) - Novia, Deni; Nadira, Diny; Melia, Sri; Rustini, Rini (Faculty of Animal Science Universitas Brawijaya, 2024)
Egg tea is a nutritious traditional drink popular in Minangkabau and West Sumatra and outside this area. Drinks usually consumed hot can be frozen to expand marketing, extend shelf life, and enjoy egg tea at low temperatures while maintaining its quality. This research proposed the physicochemical and sensory value of adding carboxymethyl cellulose (CMC) to frozen egg tea drinks. This research used an experimental, completely randomized design of five treatments and four replications. The CMC percentages were used from 0% to 0.8%. The parameters observed in the study were protein content, fat content, total solids, and sensory value. The results of the research showed that the addition of CMC to frozen egg tea drinks had a significant effect (p < 0.05) on protein content, fat content, total solids, and sensory tests (sensory value of texture and overall acceptability) but had no significant effect (p > 0.05) on sensory test for color, taste, and aroma. This research concludes that frozen egg tea drinks with the best CMC percentage was obtained by adding 0.6% CMC with a protein content of 3.09±0.25%, fat content of 1.12±0.02%, total solids of 12.13±0.18%, and a favorable sensory assessment.